Employment, technology and development : a study prepared for the International Labour Office within the framework of the World Employment Programme - Sen, Amartya; International Labour Office (Oxford : Clarendon Press, 1975)
This book describes analytical, conceptual framework and guidelines in the integration of technology in the management of development.
Includes indexes.
Bibliography: p. 165-186.
asm; 13/02/19
Loans
Keywords: Labor supply; Manpower policy; Manpower policy; Capital investments